2011
DOI: 10.1007/s11270-010-0735-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vegetation in Mitigating the Toxicity of Pesticide Mixtures in Sediments of a Wetland Mesocosm

Abstract: This study assessed effects of a mixture of two pesticides, diazinon and permethrin, on 48-h sediment toxicity to Hyalella azteca in a constructed wetland mesocosm containing non-vegetated and vegetated sections. Sediment samples were collected at inflow, middle, and back points within each section 5, 24, 72 h, 7, 14, and 21 days post-amendment. Pesticides were detected in sediments throughout non-vegetated and vegetated wetland sections. H. azteca 48-h survival varied across sampling period, wetland location,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Although previous studies have reported the mitigating effects of emergent vegetation contained within agricultural constructed wetlands and drainage ditches on the toxicity of insecticides to aquatic taxa [37], the present study appears to be the first experimental demonstration that submersed macrophytes can strongly mitigate the lethal effects of insecticides on an aquatic species. Specifically, we discovered that the common macrophyte E. canadensis substantially reduced the lethality of the popular insecticide malathion to the keystone herbivore, D. magna, [26] and also increased the rate at which water treated with malathion was detoxified.…”
Section: Discussionmentioning
confidence: 60%
“…Although previous studies have reported the mitigating effects of emergent vegetation contained within agricultural constructed wetlands and drainage ditches on the toxicity of insecticides to aquatic taxa [37], the present study appears to be the first experimental demonstration that submersed macrophytes can strongly mitigate the lethal effects of insecticides on an aquatic species. Specifically, we discovered that the common macrophyte E. canadensis substantially reduced the lethality of the popular insecticide malathion to the keystone herbivore, D. magna, [26] and also increased the rate at which water treated with malathion was detoxified.…”
Section: Discussionmentioning
confidence: 60%
“…Constructed wetland systems included horizontal flow The primary studies that showed high removal efficiencies (greater than 75%) were larger for mesocosm studies. Of the studies that analyzed the mesocosm scale, 68% had at least one contaminant removed at an efficiency greater than or equal to 75% [16,23,45 182,183,185,192,193,195,[201][202][203]209,210,[217][218][219]. Additionally, 54% of microcosm studies resulted in high removal efficiencies [30,60,76,78,83,90,94,97,119,129,131,143,146,164,168,177,181,188,194,200,207] and 59% of field studies resulted in high removal efficiencies [3,46,50,53,62,63,68,74,77,…”
Section: Scale and Type Of Wetlands Usedmentioning
confidence: 99%
“…Peak concentrations of mixed pesticides are reportedly reduced by 72% in non-vegetated CWs and 91% in vegetated CWs, representing toxic unit (TU) reductions of 79% and 95%, respectively [9]. Vegetation also plays an important role in resisting algal blooms in surface flow CWs installed to handle both nutrients and pesticides [20]. The presence of emergent vegetation is critical for managing large wetland treatment systems, especially those with low P loadings [21].…”
Section: Removal Efficiencymentioning
confidence: 99%